Repetitive and Stereotypic Phenomena and Dementia. (May 2013) - Cipriani, Gabriele; Vedovello, Marcella; Ulivi, Martina; Nuti, Angelo; Lucetti, Claudio
Background: Behavioral disturbances of dementia, such as repetitive and stereotypic phenomena, can be distressing to caregivers and may lead to early institutionalization of the patient. Objective: The purpose of this article is to examine the phenomenon of repetitive phenomena in patients with dementia. Methods: We searched the PubMed electronic databases for original research and review articles on repetitive phenomena in patients with dementia using the search terms "repetitive behavior, stereotypic behavior, dementia, Alzheimer's disease, Frontotemporal dementia." Results: Repetitive and stereotypic phenomena are common problems in dementia, which may reflect a disruption of coordinated function within the basal ganglia or corticostriatal structures. Conclusions: There are no systematic studies concerning repetitive phenomena in patients with dementia, and very little is known about the treatment. Further studies are needed to determine the specific phenomena.